Scarlet - Cogman, Genevieve (Cogman, Genevieve. Scarlet revolution novels., 2023)
"The first book in a rollicking new historical-fantasy series that reinvents the French Revolution with vampires as the aristocrats, in a lively retelling of The Scarlet Pimpernel from the author of the beloved Invisible Library series. It is 1793 and the French Revolution is in full swing. Vampires are a normal part of society across Europe--usually rich and aristocratic, they have slaked the guillotines thirst in large numbers. The mysterious Scarlet Pimpernel, a disguised British noble, and his League are heroically rescuing dozens of aristocrats and helpless victims from France, both human and vampire. Eleanor Dalton is an English housemaid working for the vampiric Baroness of Basing. Eleanor's highest aspiration is to one day become a modiste. But when the Scarlet Pimpernel and his wife come to visit, Eleanor discovers she resembles someone important. She is asked to impersonate a French aristocrat. Soon, she finds herself swept up in magic and intrigue beyond her wildest dreams"--